Comparative study on Haemodynamic response to extubation: Attenuation with Lignocaine, Esmolol, Propofol - M. H., Nagrale; Indurkar, Pradeep S.; Pardhi, Chendra Shekhar (International Journal of Research in Medical Sciences, 2016)
Background: Endotracheal extubation is an unpredictable and tricky part of anaesthetic management. Elevation in blood pressure and heart rate due to extubation are brief but may have detrimental effects. Hence there should be an effective means of attenuating sympathetic responses to tracheal extubation. Many strategies have been advocated to minimize these hemodynamic adverse responses. Among the recommended procedures i.v. lignocaine, fentanyl and esmolol appear to fulfil the above mentioned criteria. Methods: This prospective randomized study was done on 90 patients to evaluate haemodynamic effects of intravenous Propofol, Lignocaine, Esmolol given two minutes prior to extubation. Results: Heart rate, Systolic, Diastolic and Mean blood pressure decreased significantly to Esmolol 1.5mg/kg and propofol 0.5 mg/kg 2 minutes prior to extubation. With lignocaine there was an initial rise in blood pressure. Lignocaine, Esmolol and Propofol were able to attenuate cough and strain of extubation in > 90% of the patients. Regarding Esmolol, our study coincided with similar studies done by different authors but we found that esmolol in doses of 1.5mg/kg showed better results to control haemodynamic response during extubation. Sedation score was a little high in Propofol group. Extubation scoring was good with all the three drugs. Conclusions: Esmolol IV is preferred for attenuation of haemodynamic responses when compared with IV propofol 0.5 mg/kg and IV lignocaine (2%) 1 mg/kg as the attenuation effect is elicited immediately.